THE IMPORTANCE OF DIGITAL MARKETING IN THE TOURISM INDUSTRY - Kaur, Gurneet (International Journal of Research -GRANTHAALAYAH, 2017)
With the advent of superior Internet technologies, newer avenues for reaching out to target audiences have evolved. Digital marketing today has become an indispensable part of every business irrespective of its size and type. The increasing role of digital marketing has affected the way businesses promote their offerings to existing as well as new customers. The need for digital marketing has been felt like never before in the tourism industry wherein customers have instant access to all kinds of information on the latest offers and best prices. Today digital marketing plays a critical role in the success of each business which exists in the tourism industry. This paper examines the basic determinants of digital marketing and the importance of the same in the tourism industry.